2019
DOI: 10.3389/fpsyg.2018.02275
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Resilience Among Mothers and Fathers of Primary School Age Children With ASD in Malaysia: A Qualitative Constructive Grounded Theory Approach

Abstract: Little is known about the coping and resilience experiences of parents of children with autism spectrum disorder (ASD) in the Malaysian cultural context. This study utilized a qualitative methodological approach adopting constructive grounded theory. The study sought to address the lack of research to date exploring the risk and protective experiences that contribute to parental stress and resilience for parents of primary school age children with ASD in the Malaysian setting. Twenty-two parents of children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 78 publications
7
42
0
5
Order By: Relevance
“…In the case of ASD families, this study found similar results, indicating that more mothers than fathers of children with ASD suffered from anxiety (12.6% vs. 10.2%) and depression (31.7% vs 26.4%) problems. Western and eastern research, along with the current study, offer support for the notion that mothers of children with ASD experience greater stress, anxiety and depression compared with fathers [34][35][36]. Moreover, the current study found that raising a child with ASD was a significant factor with respect to anxiety and depression symptoms among mothers, but this was not the case for fathers, and paternal anxiety symptoms were not associated with the child's characteristics.…”
Section: Gender Differences In Parental Anxiety and Depressionsupporting
confidence: 71%
“…In the case of ASD families, this study found similar results, indicating that more mothers than fathers of children with ASD suffered from anxiety (12.6% vs. 10.2%) and depression (31.7% vs 26.4%) problems. Western and eastern research, along with the current study, offer support for the notion that mothers of children with ASD experience greater stress, anxiety and depression compared with fathers [34][35][36]. Moreover, the current study found that raising a child with ASD was a significant factor with respect to anxiety and depression symptoms among mothers, but this was not the case for fathers, and paternal anxiety symptoms were not associated with the child's characteristics.…”
Section: Gender Differences In Parental Anxiety and Depressionsupporting
confidence: 71%
“…First, a sample of Greek families was employed, which allowed for an exploration of the associations among the aforementioned constructs in the under-researched Greek context. Furthermore, the research was conducted among parents of healthy children, which was also a gap identified in the literature (non-Greek populations; Grant et al, 2013;Ilias, Cornish, Park, Toran, & Golden, 2019). Moreover, although negligible differences were found between mothers and fathers in terms of family resilience, parental resilience and parental well-being, the present research sought to explore gender differences and in particular, includes the paternal experience as it has been underexplored by past studies.…”
Section: Resultsmentioning
confidence: 95%
“…Linked to symbolic interactionism, grounded theory ensures to know what is happening and why in a social group ( Strauss and Corbin, 1990 ) to formulate grounded theories with empirical analysis ( Martin and Turner, 1986 ; Strauss and Corbin, 1990 ; Andrade-Rhor, 2019 ) on human behavior and the social world ( Kendall, 1999 ). This theory is especially useful when analyzing different organizations and groups ( Glaser, 1992 ) with relatively unstructured information (text data) and theoretical sampling ( Hernández-Sampieri et al, 2014 ; Ilias et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%